Survey regarding the use of endodontic posts among dentists of twin cities, Rawalpindi and Islamabad, Pakistan - Azeem, Shehroze; Zahid Mehmood; Mohibullah (Journal of the Pakistan Medical Association, 2023)
The purpose of the study was to assess the knowledge, attitude, and practices of dentists of twin cities regarding the use of endodontic posts in root canal treated tooth. A questionnaire was created and distributed among dentists of Rawalpindi and Islamabad via social media platforms regarding the use of posts. The results revealed that majority (60%) of the participants used endodontic posts for teeth with adequate ferrule, and believed that the function of endodontic posts is to retain the core material (50.5%). Glass fibre posts were preferred for anterior teeth (87%), whereas metal posts were favoured in posterior teeth (63%). It was concluded that the main function of the endodontic post is to retain the core material. The commonest indication is when there is at least 2mm of ferrule present and the optimal post length is 2/3rd of the root canal. Keywords: Post-Core Technic, Endodontically-treated tooth, Dental dowel.